2021
DOI: 10.1016/j.nicl.2021.102657
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of different iron forms in the aceruloplasminemia brain to explore iron-related neurodegeneration

Abstract: Highlights Ferrihydrite-iron is the most abundant iron form in the aceruloplasminemia brain. Iron concentrations over 1 mg/g are found in deep gray matter structures. The deep gray matter contains over three times more iron than the temporal cortex. Iron-sensitive MRI contrast is primarily driven by the amount of ferrihydrite-iron. R2* is more illustrative of the pattern of iron accumulation than QSM at 7 T.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…12 Finally, the mineral-iron map of the ACP tissue block shows a very diffuse iron load, with mean iron values of 2.57 ± 1.45 mM, in the putamen, which is about 50% lower than found by our magnetometry study-and which quantified ferritin-iron in the same structure of the same patient. 66 This is likely due to the combination of very fast relaxation times and the lack of an appropriate ROR in the slice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Finally, the mineral-iron map of the ACP tissue block shows a very diffuse iron load, with mean iron values of 2.57 ± 1.45 mM, in the putamen, which is about 50% lower than found by our magnetometry study-and which quantified ferritin-iron in the same structure of the same patient. 66 This is likely due to the combination of very fast relaxation times and the lack of an appropriate ROR in the slice.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of ceruloplasmin‐mediated oxidation of ferrous iron (Fe 2+ ) to ferric iron (Fe 3+ ) impairs iron efflux from astrocytes and leads to massive iron accumulation within these cells, whereas neurons that are mainly dependent on the supply of iron from astrocytes are probably iron‐starved 13,67 . Although ferritin‐bound iron appears to be by far the most abundant iron form in the aceruloplasminemia brain, 66,68,69 these observations are based on patients with end‐stage aceruloplasminemia, and it remains unclear how the increase in either total iron levels, as suggested by previous R2 13,70,71 and QSM studies, 70 or in the amount of ferritin‐bound iron, is associated with the clinical course of the disease. In both the ACP case and 1 of the HD cases, it is noticeable that R2 appears, in a first instance, to be a better marker for iron than QSM, whereas the situation is clearly different in the AD case.…”
Section: Discussionmentioning
confidence: 99%
“…Aging ↑ serum ferritin [53] ↑ Fe in red nucleus, putamen, substantia nigra, dentate nucleus, globus pallidus, caudate nucleus, subthalamic nucleus, cortex [7] Fe remains stable in oligodendroglia; Fe accumulates in astrocytes and dystrophic microglia in cortex and deep gray matter [12] Fe bound to ferritin in cytoplasm of microglia and astrocytes and to neuromelanin in neurons [12,28] AceruloplasMinemia ↑ Fe in liver, pancreas, retina ↑ serum ferritin, ↓ transferrin saturation [54,55] ↑ Fe in putamen, caudate, lateral, habenular, and pulvinar thalamic nuclei, red nucleus, dentate nucleus, inner cortical layers, hippocampus, mammillary bodies, superior and inferior colliculi [56,57] ↑ Fe in astrocytes, neurons [58][59][60] Fe stored in ferritin/ hemosiderin in lysosomal dense bodies and cytoplasmic inclusions [61,62] Hereditary Ferritinopathy ↑ Fe in liver, kidney, skin, muscle ↓ serum ferritin [63][64][65] ↑ Fe in globus pallidus, substantia nigra, dentate nucleus, putamen, thalamus, caudate, deep cortical layers [66][67][68] ↑ Fe in nuclei and cytoplasm of microglia, oligodendroglia, neurons, and also extracellularly [64,69] Fe stored in inclusion bodies consisting of abnormal ferritin aggregates [69,70] Pantothenate Kinase-Associated Neurodegeneration -↑ Fe in globus pallidus, substantia nigra [71][72][73][74] ↑ Fe in astrocytes, neurons, perivascular macrophages, iron dust in neuropil [75,76] Fe stored in cytoplasmic inclusions co-localized with ferritin [75] Mitochondrial Membrane Protein-Associated Neurodegeneration -↑ Fe in globus pallidus, substantia nigra, putamen, caudate [77,78] ↑ Fe in perivascular macrophages, astrocytes, neurons…”
Section: Macroscopic Cellular Subcellularmentioning
confidence: 99%
“…Additionally, Fe accumulation also affects the lateral habenula, mammillary bodies, superior and inferior colliculi, and hippocampus [56]. Ex-vivo examination of brain tissue using quantitative MRI, Electron Paramagnetic Resonance (EPR), and Superconducting Quantum Interference Device (SQUID) magnetometry showed that more than 90% of accumulated Fe is deposited as ferrihydrite-Fe in ferritin and hemosiderin which are the main drivers of increased R2* relaxivity and susceptibility; the remaining part of Fe was found to be embedded in oxidized magnetite/maghemite minerals with ferrimagnetic properties [61]. Iron accumulation in putamen may rarely be accompanied with cavitation [149].…”
Section: Neurodegenerations With Brain Iron Accumulation (Nbia) Groupmentioning
confidence: 99%
“…To achieve sensing of different redox states of iron, various methods have been explored but with limited success either in living cells or in vivo. For example, laboratory techniques, such as inductively coupled plasma mass spectrometry ( 12 , 13 ), electron paramagnetic resonance ( 14 ), x-ray fluorescence ( 15 ), and magnetic resonance imaging (MRI) ( 16 18 ) have been developed but cannot readily provide spatial or temporal information in vivo because of their restrictive requirements for sample pretreatment or excessive time needed for data collection. It has been shown that “labile” iron pools, which comprise only a small portion of total iron, play critical roles in many cellular processes, including lipid oxidation during ferroptosis and generating free radicals in AD ( 19 21 ), and all of the above methods can measure only the total iron without differentiating labile iron pools.…”
Section: Introductionmentioning
confidence: 99%